Digestibility of soybean oil and rape oil by swine - Paloheimo, L.; Jahkola, Berit (Agricultural and Food Science, 1959)
The digestion experiment was made with two pigs. The Cr2O3 ratio technique was used. The basic ration consisted of 2.6 kg skimmilk and 1.6 kg of a concentrate mixture. The animals received in alternate periods soybean oil and rape oil. The digestibility of the oils was investigated on 3 different levels: 100 g, 200 g, and 300 g per day per animal. No significant difference in the digestibility of the two oils could be detected. The digestibility percentage was about 100. Increasing the oil allowances resulted in a slight decrease in the digestibility. The digestibility of rape oil appeared to be very slightly inferior to that of soybean oil.